2017
DOI: 10.4269/ajtmh.16-0731
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2a, Open-Label, 4-Escalating-Dose, Randomized Multicenter Study Evaluating the Safety and Activity of Ferroquine (SSR97193) Plus Artesunate, versus Amodiaquine Plus Artesunate, in African Adult Men with Uncomplicated Plasmodium falciparum Malaria

Abstract: Artemisinin-based combination therapies are recommended as first-line agents for treating uncomplicated malaria. Ferroquine, a 4-aminoquinolone, is a novel long-acting combination partner for fast-acting drugs like artesunate (AS). We did a small phase 2a, multicenter, open-label, safety-focused dose-ranging randomized study of ferroquine at three African hospitals: two Gabonese and one Kenyan. We recruited adult men with symptomatic uncomplicated monoinfection. Four escalating doses of ferroquine (100, 200, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…WLL-vs is of particular interest given its selectivity for the parasite proteasome and the fact that resistance is rare and low-grade (Li et al, 2016;Stokes et al, 2019;Yoo et al, 2018). Ferroquine has shown promising efficacy in phase II trials (Supan et al, 2017) and our assays indicated a unique ring-active profile that underscores its potential. With GNF-Pf-5660, chemical derivatization efforts are underway to improve its partial in vivo efficacy, established in rodent malaria models (Vanaerschot et al, 2017).…”
Section: Figure 7 Metabolic Profiling Of Compounds Identified Cellular Processes Targeted By Compoundsmentioning
confidence: 82%
See 1 more Smart Citation
“…WLL-vs is of particular interest given its selectivity for the parasite proteasome and the fact that resistance is rare and low-grade (Li et al, 2016;Stokes et al, 2019;Yoo et al, 2018). Ferroquine has shown promising efficacy in phase II trials (Supan et al, 2017) and our assays indicated a unique ring-active profile that underscores its potential. With GNF-Pf-5660, chemical derivatization efforts are underway to improve its partial in vivo efficacy, established in rodent malaria models (Vanaerschot et al, 2017).…”
Section: Figure 7 Metabolic Profiling Of Compounds Identified Cellular Processes Targeted By Compoundsmentioning
confidence: 82%
“…Methylene blue, in contrast to piperaquine, is also potent against mature gametocytes that are not thought to degrade hemoglobin (Adjalley et al, 2011), implying an additional mode of action for methylene blue that might affect additional redox cycling agents such as NADPH levels (Siciliano et al, 2017). Interestingly, ferroquine and naphthoquine, which are both chloroquine derivatives that are currently part of artemisininbased combination therapies under clinical trials (Isba et al, 2015;Supan et al, 2017), shared a unique stage specificity profile showing peak activity during early rings and a gradual increase of IC 50 8h values through to schizonts (Figure 2). Ferroquine has hemozoin inhibitory activity similar to chloroquine and has been shown to induce the formation of hydroxyl radicals via the Fenton reaction, leading to lipid peroxidation and exacerbating oxidative stress in the parasite (Atamna and Ginsburg, 1993;Chavain et al, 2008;Dubar et al, 2008).…”
Section: Figure 7 Metabolic Profiling Of Compounds Identified Cellular Processes Targeted By Compoundsmentioning
confidence: 99%
“…Piperaquine (18), another 4-aminoquinoline, is currently part of an ACT treatment regimen with 3 in a fixed-dose combination, which has shown excellent tolerability and high malaria cure rates. [22][23][24] Discovered more recently is ferroquine (19), which has completed phase IIa clinical trials, 25 and has recently shown efficacy in combination with 1. 26…”
Section: Chemotherapymentioning
confidence: 99%
“…Thus, future patients treated with ferroquine must have their hepatic and cardiac profiles monitored. (42,43) Cipargamin (Fig. 5 -NITD609, Novartis ® ) is a spiroindolone in Phase II clinical trials.…”
Section: Malaria Chemotherapymentioning
confidence: 99%
“…Thus, future patients treated with ferroquine must have their hepatic and cardiac profiles monitored. 42 , 43 …”
mentioning
confidence: 99%